RADIATION DAMAGE AND ALTERATION OF ZIRCON FROM A 3.3 GA PORPHYRITIC GRANITE FROM THE JACK HILLS, WESTERN AUSTRALIA - Utsunomiya S.; Ewing R.C.; Valley J.W.; Cavosie A.J.; Wilde S.A. (My University, 2007)
Complexly zoned zircons (19 grains, ~ 3.3 Ga) from a porphyritic granite in the Jack Hills, Western Australia, have been investigated using electron microprobe analysis (EMPA) and transmission electron microscopy (TEM) in order to examine the effects of radiation as a function of dose, as well as the nano-scale microstructure and composition of impurities and secondary alteration phases. In back-scattered electron (BSE) images, zones with bright contrast consist of an almost unaltered zircon with limited amounts of impurity elements. In contrast, the dark zones contain higher concentrations of trace elements: U, Th, Pb, Fe, Y, Ce, Ca and Al. The cumulative doses due to alpha-decay in the dark zones are calculated to be 0.21-1.0 × 1017 (alpha-decay events/mg), equivalent to 1.0-4.7 dpa (displacements per atom). These doses are much higher than the dose required for radiation-induced amorphization, as determined by ion-beam irradiation of synthetic zircon, 0.3-1.0 dpa (0-600 °C). However, based on high-resolution TEM observations, none of the zircons are fully amorphous, to the result of annealing under ambient conditions. The concentrations of Ca and Al, which was considered to indicate alteration, increase dramatically at a cumulative dose of 1.6 × 1016 (alpha-decay events/mg). This is the dose at which the first percolation point occurs, as amorphous domains overlap and form an interconnected network. In the altered zones, nanocrystallites of zircon are present with a random orientation, and the amorphous matrix contains the impurity elements. Although the Ce-concentration is extremely high, 1-2 wt.%, the Ce anomaly, Ce/Ce*, does not vary significantly as a function of dose or degree of alteration, indicating that the LREE patterns were overprinted by the fluids with a similar Ce-anomaly. The valence of Ce analyzed by EELS (electron energy loss spectroscopy) is tetravalent in the altered zone, suggesting that the altering fluids were oxidizing. © 2006 Elsevier B.V. All rights reserved.
Keywords: ALTERATION; EELS; JACK HILLS; RADIATION DAMAGE; TEM; ZIRCON